Increasing Physical Activity in Schools: Strategies for School Health Practitioners. Issue 5 (September 2019) - Kelly, Cheryl; Carpenter, Dick; Behrens, Timothy K.; Field, Julaine; Luna, Carmen; Tucker, Elizabeth; Holeva-Eklund, Whitney M.
Background . Colorado passed House Bill 11-1069 in 2011 requiring all public elementary schools to provide students with a minimum of 30 minutes of physical activity (PA) per school day (Physical Activity Expectation in Schools, 2011). The purpose of this article is to describe the results of a 3-year initiative to increase opportunities for PA and to provide recommendations for school health practitioners implementing similar programming. Intervention. In 2014, 13 school districts were funded to increase student PA during school hours and before and after school hours. Intervention activities spanned all components of the Comprehensive School Physical Activity Program framework. An evaluation was conducted to estimate the number of schools providing at least 30 minutes of PA a day. A mixed methods evaluation design was implemented that included tracking the number of minutes of PA provided before, during, and after school and semistructured interviews with school health coordinators. Results. In Year 1, an average of 48 minutes of PA were provided per day. By the end of year 3, the average minutes of PA doubled to 90 minutes per day. Teachers and staff identified professional development and administrator support as key components to incorporating more PA throughout the school day. Conclusions. Health promotion interventions in schools can increase access to PA opportunities for students. Sustainability of PA efforts in schools is dependent on funding to support professional development for teachers and staff and building administrative support for school-based PA.